HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN DIARE PADA BAYI 0-6 BULAN - Danawati, Ni Kadek Ayu Sri; Budiani, Ni Nyoman; Erawati, Ni Luh Putu Sri (Fakultas Ilmu Kesehatan, 2025)
Diarrhea is a symptom of infection in the intestinal tract, which can be caused by various bacterial, viral, and parasitic organisms. Many factors influence the occurrence of diarrhea in infants, one of which is the lack of exclusive breastfeeding. This study aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 0-6 months in the working area of Banjarangkan I Community Health Center. This research uses a correlational analytical study design where the principle is to compare the risk of disease between groups exposed and not exposed to the research factor. The research approach used is cross-sectional. The study was conducted at the Banjarangkan I Community Health Center, Banjarangkan District, Klungkung Regency, with a total of 66 respondents consisting of infants aged 0-6 months in April 2024. Data collection was carried out using questionnaires and analyzed using univariate analysis, bivariate analysis, and Odds Ratio (OR) with SPSS Version 25 software. The results of the analysis showed that the incidence of diarrhea in babies who were exclusively breastfed was 5 respondents (13,9%) compared to babies who were not exclusively breastfed as many as 13 respondents (43.3%) and this difference was significant with an Odds Ratio (OR) value of 0.211 and the p value of 0.008 < 0.05. There is a relationship between exclusive breastfeeding and the incidence of diarrhea in babies 0-6 months. Breastfeeding reduces the incidence of diarrhea in infants.